Intracellular Signal Triggered by Cholera Toxin in Saccharomyces boulardii and Saccharomyces cerevisiae - Brandão, Rogelio L. (American Society for Microbiology, 1998)
As is the case for Saccharomyces boulardii, Saccharomyces cerevisiae W303 protects Fisher rats against cholera toxin (CT). The addition of glucose or dinitrophenol to cells of S. boulardii grown on a nonfermentable carbon source activated trehalase in a manner similar to that observed for S. cerevisiae. The addition of CT to the same cells also resulted in trehalase activation. Experiments performed separately on the A and B subunits of CT showed that both are necessary for activation. Similarly, the addition of CT but not of its separate subunits led to a cyclic AMP (cAMP) signal in both S. boulardii and S. cerevisiae. These data suggest that trehalase stimulation by CT probably occurred through the cAMP-mediated protein phosphorylation cascade. The requirement of CT subunit B for both the cAMP signal and trehalase activation indicates the presence of a specific receptor on the yeasts able to bind to the toxin, a situation similar to that observed for mammalian cells. This hypothesis was reinforced by experiments with (125)I-labeled CT showing specific binding of the toxin to yeast cells. The adhesion of CT to a receptor on the yeast surface through the B subunit and internalization of the A subunit (necessary for the cAMP signal and trehalase activation) could be one more mechanism explaining protection against the toxin observed for rats treated with yeasts.